Clinical outcomes in metaphyseal locking plate fixation of distal femur and proximal tibia fracture - Y Kale, Sachin; D Singh, Shikhar; Padmawar, Shubham; Patel, Ibad; Ahmed, Sohrab; B. Dhar, Sanjay (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Introduction: Fracture of distal femur and proximal tibial are often difficult to treat and associated with many complications. We aimed to assess the clinical and radiological union time and functional outcome in fractures of distal femur and proximal tibia managed by metaphyseal locking plates and to study the complications associated with it. Methodology: This prospective study was conducted from June 2014 to October 2016 in the Department of Orthopedics, Dr. DY Patil Medical College, Hospital and Research Centre, Nerul, Navi Mumbai, using a consecutive sample of 50 patients fulfilling our study eligibility. Detailed clinical history of the patients and operative details were noted. All patients were followed up at 3 and 6 months, and were assessed for pain, range of movement (ROM), functional outcomes, union times and complications. Results: Distal femur fracture were seen in 42% cases (most common type A2) while proximal tibia fractures were seen in 58% cases (most common type II). 28.6% patients showed fracture union by 5 months, 85.74% showed union by 6 months. Complaint of pain at 3 months was given by 22% cases and at 6 months by 6% cases. Delayed, mal and non-union were seen in 12%, 4% and 2% of cases respectively. As per the Oxford Knee Score, excellent outcome was seen in 86% cases while good and fair outcome was seen in 8% and 6% cases respectively. Conclusion: Metaphyseal locking plates is a superior implant for the fractures around knee with an excellent functional outcome.